An integrated approach to planning, assessing and implementing the removal of topsoil: from regulations to evidence-based land management practices - Koshel, A.; Kolhanova, I.; Kempa, O. (Land Management, Cadastre and Land Monitoring, 2025)
Scientific and methodological approaches to the development of land protection measures in modern land management documentation are proposed.The article considers modern requirements for the development of working land management projects for the removal and transfer of the fertile soil layer in accordance with the regulatory framework of Ukraine. The main tasks of such projects are outlined, including ensuring the rational use and preservation of soil fertility, minimizing the negative consequences of economic activity and restoring disturbed lands. An analysis of key indicators that determine the feasibility of removing and storing soil layers is carried out: humus content, acidity, exchangeable sodium content and granulometric composition. It is shown that compliance with these parameters is an important factor in environmental safety and sustainable development of agricultural production.The content of land management working projects includes design tasks, an explanatory note, a description of natural conditions, the results of soil and geodetic surveys, design decisions for determining a set of land protection measures, plans for agricultural soil groups and calculations of the estimated cost of work. Such a structure ensures the scientific validity of decisions and the practical effectiveness of their implementation.The article summarizes current knowledge and practices in the field of land management, offering a comprehensive approach to the development of land management working projects. The proposed rules and recommendations can serve as a basis for specialists engaged in land management, agronomy and ecology.Keywords: land protection, land management, land improvement, land management, land management documentation, topsoil removal, land management working project.
Keywords: land protection; land management; land improvement; management of land resources; land management documentation; removal of fertile soil layer; working draft of land management